Examining Rural School Implementation of Positive Behavioral Supports Across Tiers. (September 2022) - Chaparro, Erin A.; Kittelman, Angus; McDaniel, Sara C.; Peshak George, Heather; VanLone, Janet; So, SoLing
Positive Behavioral Interventions and Supports (PBIS) is a prevention-oriented multitiered system of support. In this article, we discuss how PBIS implementation might be different for schools in rural settings. We used two subsamples of an extant data set of 11, 561 schools in 44 U.S. states reporting on PBIS implementation fidelity during the 2018-19 school year. We examined PBIS implementation in rural and nonrural settings using a subsample of 6, 631 schools during their first five years of PBIS implementation (2014-15 to 2018-19 school years). Further, we used a subsample of 2, 266 schools to examine differences in implementation for rural schools, specifically ( n = 1, 215) in their first five years of PBIS implementation (2014-15 to 2018-19) compared to rural schools ( n = 1, 051) implementing six or more years (2000-01 to 2013-14). Rural schools differ from other school locales in the implementation of Tiers 2 and 3 systems during initial implementation. When examining the implementation in rural schools implementing PBIS for five or fewer years to those implementing for six years or more, those implementing longer had higher scores at Tiers 2 and 3. Practical implications across all three tiers, special education, and rural locales are presented.